Responses to 101 questions on Islam - Renard, John 1944- (Paulists Press, 1998)
Answers questions about the religious traditions of Islam and Muslims, arranged in such categories as Beginnings and Sources, History and Development, Beliefs and Practices, Law and Ethics, Cultural and Intellectual Themes, Women and the Family, and more.